Effect of foulants on arsenic rejection via polyacrylonitrile ultrafiltration (UF) membrane - Agarwal, Gopal P.; Karan, Raj; Bharti, Sachin; Kumar, Hemant; Jhunjhunwala, Sumit; Sreekrishnan, T. R.; Kharul, Ulhas K. (Desalination, 2013)
Arsenic rejection via modified polyacrylonitrile ultrafiltration (UF) membrane was found to be very high, however, the presence of commonly found foulants in arsenic solution affected membrane performance. The effect of commonly found foulants, such as ovalbumin, humic acid and egg white on arsenic rejection were studied. Experiments indicated that the As(V) rejection was affected by the total quantity of proteins and not the variety of proteins present in a solution. As(V) rejection was found to decrease with increasing proteins while fouling was found to increase from 25% for 0.1 mg/ml to 33% for 0.5 mg/ml egg white. The As(V) rejection was found to decrease with increasing concentration of humic acid for PAN membranes. Fouling studies showed that humic acid was a lesser foulant in comparison to egg white. However a combination of the two foulants led to a decrease in the overall fouling. pH was also found to be a very important factor for egg white dissolution and As(V) rejection. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Arsenic rejection; Egg white; Humic acid; Ovalbumin; Polyacrylonitrile; Ultrafiltration